Vertical Electrical Soundings for Locating Groundwater Potential Zones in Osmania University Campus, Hyderabad, Telangana State, India - Kumar, D. Vijay; Ramadass, G. (Journal of Experimental Sciences, 2015)
Based on the resistivity investigations Osmania University Campus, precisely depth and resistivity of subsurface layers were computed, Various geoelectric sections along different profiels (I to VIII) was obtained and analyzed. The study area is showing four layered geoelectrical sections, the top soil layer of variable resisitivity value between 11.2 to 599 Ωm, whose maximum thickness is 0.75 to 4.45 m. The highly weathered second layer resistivity value varing from1.72 to 1800 Ωm. And thickness is 0.12 to 36.6m. The third fractured layer indicated by resistivity value 16.3 to 46074 Ωm and thickness is 4.9 to 87.4 m. The basement that is associated with hard rock and very high resistivities ranging to infinity. The low restivity with thick overbuden and fractured bed rock constitute the aquifer units and the series of basementt undulations identified from the geolelectrical sections are potential points for groundwater locations.